How and why do young soccer players change the Flow State? - Castillo-Rodriguez, A.; Ureña Lopera, C.; Onetti-Onetti, W.; Chinchilla-Minguet, J. L. (PLOS ONE, 2020)
Flow State (FS) as well as other psychological characteristics influence sports performance (SP) and could be relevant according to the playing position in team sports, such as the soccer where players have different specific functions within the team. The aim of this study was to evaluate the difference in FS dimensions in young soccer players between training time (TR) and official competition time (CM), according to the playing position and, to find relationships between FS dimensions and physical characteristics and academic performance. A total of 141 U16 soccer players were selected (14.7 ± 0.5 years). Data was collected for academic performance, physical and socio-demographic characteristics, and on two occasions, the dimensions of FS (before of a TR and CM). The results showed that the FS dimensions are higher before of the TR than before of the CM (p < 0.05) in all playing positions. In clear goals dimension, forwards showed lower scores than other playing positions, and various dimensions had a positive relationship with academic performance. In conclusion, the FS presented in CM is lower in U16 soccer players compared to that presented in TR. This work has contributed to increasing the knowledge of the fluctuation of the FS that negatively influence the soccer player in pre-competition states and the influence of various factors on this construct.